Evaluation of dense Pd–Ag membrane reactor performance during methanol steam reforming in comparison with autothermal reforming using CFD analysis. (1st June 2016) - Ghasemzadeh, K.; Andalib, E.; Basile, A.
Abstract: This study presents a 2D-axisymmetric computational fluid dynamic (CFD) model to investigate the performance of dense Pd–Ag MR during methanol steam reforming (MSR) in comparison with methanol autothermal reforming (MATR) reaction for hydrogen production. The proposed CFD model provided the local information of velocity, pressure and component concentration for the driving force analysis. After investigation of mesh independency of CFD model, the validation of dense Pd–Ag MR during MSR reaction was carried out by experimental data and a good agreement between modeling results and experimental data was achieved. In the MR model, a dense Pd–Ag membrane with 50 μm thickness and also a commercial Cu/ZnO/Al2 O3 catalyst in reaction zone were considered. The effects of the some important operating parameters (temperature, pressure and sweep gas ratio) on the performances of Pd–Ag MR were studied in terms of methanol conversion and hydrogen recovery. The CFD results showed that the Pd–Ag MR during MATR reaction presents higher performance in term of the methanol conversion and hydrogen recovery with respect to once obtained in the MSR reaction. In particular, in the best operating condition, hydrogen production rate in reaction zone show an enhancement around 11% in the MATR reaction over once achieved in the MSR reaction. Highlights: Pd–Ag MR performance was investigated during MSR in comparison with MATR reaction using CFD analysis. The effects of some operating parameters on Pd–Ag MR performance was evaluated for H2 production in the MSR and MATR reactions. CFD method as a promising modeling tool can be used for estimation of MR performance during reforming reactions.